The Influence of Location on Purchase Decisions Through Increasing Sales Volume - Karim, Ahmad (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
Intense competition in the business world requires companies to be able to develop their businesses continuously innovate and make new breakthroughs. This research aims to examine variables that influence purchasing decisions and consumer satisfaction, namely location and price variables to increase sales volume. This research uses quantitative methods using primary data. The sampling method used in this research is a non-probability sampling method, with the Accidental Sampling technique which is a technique for determining samples by chance. The sample in this study amounted to 97 respondents. The results of the T model 1 test can be seen in Table 4.22, namely with a beta coefficient value of 0.471 which shows a positive direction with a significance value of 0.000 which is smaller than the significance level of 0.05. This shows that location (X1) has a positive and significant effect on purchasing decisions (Y1). The second hypothesis proposed in this research states that sales volume moderates the relationship between location and purchasing decisions at the Simpang Tiga Tanjung Morawa Restaurant. The test results can be seen in the location variable, the parameter coefficient value is 3.594 with a significance value of 0.002. The interaction variable X1 obtained a parameter coefficient of -0.070 with a significance value of 0.007. Future researchers can retest consistency or add new variables that were not examined in this research.